A descriptive study to assess factors affecting core indicators of infant and young child feeding practices in urban area of Gujarat State, India - Rana, Bhavik M.; Chandwani, Haresh; Sonaliya, K. N.; Prajapati, Arpit (International Journal Of Community Medicine And Public Health, 2017)
Background: Infant and young child feeding (IYCF) practices followed by mother during first 2 years of her child directly affect the health status of the child in the long run. To reduce the infant and under five mortality rate it is imperative that mothers practice appropriate IYCF practices as guided by World Health Organization. The main objective of the study was to assess the factors affecting IYCF practices among sampled population. Methodology: Current cross sectional study was conducted with sample comprising 300 mothers having children aged 0-23 months. Early initiation of breastfeeding, Pre lacteal feeding, exclusive breastfeeding and predominant breastfeeding practices followed by mothers, were analyzed in the current study. Results: Around 88% children were started early breast feeding. The number of mothers who gave pre-lacteal feed to their new born was 11 (2.75%). 281(66%) mothers out of the sampled population were giving exclusive breast feeding. Only 12 (3%) study population was providing predominant breast feeding. The socio-demographic characteristics like education of mother, maturity of nursing mother, socio economic class of mother and antenatal care received by mother were found significantly affecting these practices. Conclusion: The indicators for the exclusive breast feeding practices are not at the desired level. There is need to improve the knowledge of mothers regarding IYCF practices.